KEPASTIAN HUKUM KEKUATAN AKTA OTENTIK TERHADAP PARA PENGHADAP YANG MENGANDUNG KLAUSULA EKSONERASI DIKAITKAN DENGAN TANGGUNG JAWAB NOTARIS. - Prianto, Agung; Halim, Anriz Nazaruddin; Kumala, Yudha Cahya (LPPM Institut Pendidikan Nusantara Global, 2024)
Notaries are authorised to make authentic deeds and other authorities as referred to in Law Number 2 of 2014 on the Amendment to Law Number 30 of 2004 on the Office of Notary. Article 1338 of the Civil Code regarding the principle of freedom of contract and Article 1337 of the Civil Code regarding halal causa. In carrying out their duties and positions, Notaries embed exoneration clauses in their deeds as a form of vigilance from matters arising from the parties in their deeds. The theories used in this research are Hans Kelsen theory of responsibility and Jan Michael Otto theory of legal certainty. The method used in this research is normative juridical law supported by interviews, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The research approaches used are statute approach, conceptual approach, analytical approach, and case approach. The technique of collecting legal materials is carried out by identifying and inventorying positive legal rules, examining library materials (books, scientific journals, research reports), and other sources of legal materials. The technique of analysing legal materials is carried out by systematic interpretation. From the research conducted by the author, it can be concluded that the responsibility that can be imposed on the Notary is the responsibility based on the fault of the Notary. That a Notary is responsible for his or her own offence and not the offence committed by the confronters. As well as the legal certainty of an authentic deed made before a Notary as a public official containing an exoneration clause that the inclusion of an exoneration clause in the Notary deed is not explicitly regulated in the Notary Office Law regarding whether or not the use of the clause is prohibited. Therefore, the inclusion of the exoneration clause may or may not exist in the Notarial deed, and the inclusion of the exoneration clause is intended to anticipate any manipulation or fraud committed by the parties.